NEW EMPIRICAL FORMULAE OF UNDERTOW VELOCITY ON MIXED AND GRAVEL BEACHES - Christos antoniadis (JOURNAL OF COASTAL DEVELOPMENT, 2013)
This paper reports a series of 3-dimensional physical model tests to measure cross-shore current data, generated by oblique wave attack, along gravel and mixed beaches with a uniform slope and a trench. Coastal managers and coastal engineers are beginning to give attention to gravel and mixed beaches due to the fact that they are two of the most effective natural sea defences.There is a need, from a scientific and coastal management perspective to have a deeper understanding of how gravel and mixed beaches operate.The studies described in this paper aim to investigate the behaviour of the undertow velocity on mixed and gravel beaches. Existing formulae have been used to predict the experimental results and new equations for predicting the undertow velocity under these conditions are proposed. The new empirical formulae predict time- and depth-averaged undertow and are based on a nonlinear regression of a modification of the Grasmeijer’s and Ruessink’s model where the zones where divided based on the related distance of the point of interest and the breaking point. Verification with large-scale experiments showed that the new formulae predicted well the undertow velocities on mixed and gravel beach with trench and uniform slope.